Sosialisasi Materi Literasi Keuangan dalam Pencatatan Keuangan Pribadi pada Siswa/i SMAN 8 Tambun Selatan - Ossi Ferli; Antyo Pracoyo; Oktavia Ramadaniyah; Denni Samuel Rajagukguk; Ratna Nilanjana Kurniathena (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This community service activity aims to improve financial literacy among students of SMAN 8 Tambun Selatan through socialization of personal financial records. Based on initial identification, it was found that many students did not understand the importance of recording income and expenses, and were not used to preparing a monthly budget. Through an interactive counseling approach and evaluation questionnaire, students were provided with an understanding of the basic concepts of financial management, the importance of distinguishing needs and wants, and the practice of daily financial records. The evaluation results showed that 96.6% of students understood the material presented, and more than 60% expressed interest in starting regular financial records. This activity proves that financial literacy education can encourage changes in attitudes and financial behavior that are wiser from school age.